Precision strikes: PSMA-targeted radionuclide therapy in prostate cancer – a narrative review - Szponar, Paweł; Petrasz, Piotr; Brzeźniakiewicz-Janus, Katarzyna; Drewa, Tomasz; Zorga, Piotr; Adamowicz, Jan (Frontiers in Oncology, 2023)
Introduction: Radio-ligand targeted therapy is a new and promising concept of treatment Castration resistant prostate cancer (CRPC). Only a few radio-pharmaceutics were approved for usage in treating prostate cancer, among the multiple others tested. We aimed to review and summarize the literature on the therapeutic isotopes specific for PSMA. Methods: We performed a scoping literature review of PubMed from January 1996 to December 2022. Results: 98 publications were selected for inclusion in this review. The studies contained in publications allowed to summarize the data on pharmacokinetics, therapeutic effects, side effects and the medical use of 225Ac and 177Lu radionuclides. The review also presents new research directions for specific PSMA radionuclides. Conclusions: Radioligand targeted therapy is a new and promising concept where Lu-177-PSMA-617 have promising outcomes in treatment according to standard of care.